Potensi Ekstrak Akar Manis (Glycyrrhiza glabra L.) untuk Pengobatan Hiperpigmentasi: Tinjauan Pustaka - Sianturi, Ester Yulyana; Primayanti, I Dewa Ayu Inten Dwi (Cermin Dunia Kedokteran, 2025)
Hyperpigmentation is a dermatological condition characterized by increased melanin production which is the pigment responsible for skin color. Melanin is synthesized by melanocytes through an enzymatic pathway regulated by the enzyme tyrosinase. This process can be triggered by various factors such as ultraviolet (UV) radiation, hormonal changes, skin inflammation, aging, and the use of certain medications. One therapeutic approach is the use of natural ingredients, including herbal plant extracts. Glycyrrhiza glabra L., commonly known as licorice root, has long been used in both traditional and modern medicine due to its active compounds such as glabridin, which possesses antioxidant and tyrosinase-inhibiting properties. This review aims to evaluate the potential of licorice root extract as a natural depigmenting agent in the treatment of hyperpigmentation. A literature review was conductedusing databases PubMed, Google Scholar, NCBI, and ResearchGate. The findings indicate that glabridin selectively inhibits tyrosinase activity without causing skin irritation and also exhibits anti-inflammatory and photoprotective effects. Licorice root extract showspromise as a safe and effective natural therapeutic option for managing hyperpigmentation.